ICOADS Release 3.0: a major update to the historical marine climate record. (27th June 2016) - Freeman, Eric; Woodruff, Scott D.; Worley, Steven J.; Lubker, Sandra J.; Kent, Elizabeth C.; Angel, William E.; Berry, David I.; Brohan, Philip; Eastman, Ryan; Gates, Lydia; Gloeden, Wolfgang; Ji, Zaihua; et al.
ABSTRACT: We highlight improvements to the International Comprehensive Ocean‐Atmosphere Data Set (ICOADS) in the latest Release 3.0 (R3.0; covering 1662–2014). ICOADS is the most widely used freely available collection of surface marine observations, providing data for the construction of gridded analyses of sea surface temperature, estimates of air–sea interaction and other meteorological variables. ICOADS observations are assimilated into all major atmospheric, oceanic and coupled reanalyses, further widening its impact. R3.0 therefore includes changes designed to enable effective exchange of information describing data quality between ICOADS, reanalysis centres, data set developers, scientists and the public. These user‐driven innovations include the assignment of a unique identifier ( UID ) to each marine report – to enable tracing of observations, linking with reports and improved data sharing. Other revisions and extensions of the ICOADS' International Maritime Meteorological Archive common data format incorporate new near‐surface oceanographic data elements and cloud parameters. Many new input data sources have been assembled, and updates and improvements to existing data sources, or removal of erroneous data, made. Coupled with enhanced 'preliminary' monthly data and product extensions past 2014, R3.0 provides improved support of climate assessment and monitoring, reanalyses and near‐real‐time applications.